2018
DOI: 10.3171/2018.1.spine17993
|View full text |Cite
|
Sign up to set email alerts
|

Radiological adjacent-segment degeneration in L4–5 spondylolisthesis: comparison between dynamic stabilization and minimally invasive transforaminal lumbar interbody fusion

Abstract: OBJECTIVEPedicle screw–based dynamic stabilization has been an alternative to conventional lumbar fusion for the surgical management of low-grade spondylolisthesis. However, the true effect of dynamic stabilization on adjacent-segment degeneration (ASD) remains undetermined. Authors of this study aimed to investigate the incidence of ASD and to compare the clinical outcomes of dynamic stabilization and minimally invasive transforaminal lumbar interbody fusion (MI-TLIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Furthermore we did not see any adjacent-segment degeneration, which is frequently seen even after motion-preserving instrumented procedures. 17 The analysis to find any preoperative predictors of instability did not show that disc height could be predictive. Although our findings are extremely limited by the size of our group, they corroborate the findings of Schär et al 25 The limitations of our study are obvious (small number, retrospective nature, selection bias related to patients' ability to get to the study facility).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore we did not see any adjacent-segment degeneration, which is frequently seen even after motion-preserving instrumented procedures. 17 The analysis to find any preoperative predictors of instability did not show that disc height could be predictive. Although our findings are extremely limited by the size of our group, they corroborate the findings of Schär et al 25 The limitations of our study are obvious (small number, retrospective nature, selection bias related to patients' ability to get to the study facility).…”
Section: Discussionmentioning
confidence: 92%
“…We conducted studies to compare lumbar fusion with dynamic stabilization with an average follow-up of more than 2 years. 14,15 Kuo et al first examined 86 patients with L4-5 spondylolisthesis and demonstrated that the clinical and radiological outcomes of DDS were similar to those of minimally invasive transforaminal lumbar interbody fusion (mi-TLIF) for grade I spondylolisthesis after approximately 2.5 years postoperatively. Although DDS might be an alternative to standard arthrodesis in mild lumbar spondylolisthesis, the dynamic pedicle screws could have other issues like wearing and loosening in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the patients in the series required secondary surgery, a longer follow-up and a larger number of patients would be necessary to corroborate the protective effect of DDS against ASD. 15 The current study aimed specifically to investigate the differences among patients with and without spondylolisthesis after dynamic stabilization and thus did not include patients who underwent lumbar fusions. It remains elusive how spondylolisthesis might affect the theoretical benefit of DDS in the amelioration of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the issue of adjacent-segment degeneration (ASD), our group previously published a study to address ASD and found that the dynamic stabilization would lead to a lower chance of adjacent disc degeneration in comparison with interbody fusion [ 27 ]. The paper concluded that the clinical improvements after Dynesys were similar to those following fusion for L4–5 Meyerding grade I degenerative spondylolisthesis at 3-year postoperation.…”
Section: Discussionmentioning
confidence: 99%